Textile Production in Classical Attica: A brief PhD Thesis Summary - Spentidaki, Stella (Archaeological Textiles Review, 2013)
This study examined textile production in Attica with an interdisciplinary method, which combined information from the written sources, iconography, textile production tools and textile remains, in order to establish the most complete image possible of the textile activity in the Classical period. These sources inform us of an elaborate textile production and a division of labour in this domain. The Greeks have inherited a great textile tradition and technical knowledge, which, combined with their familiarity of the natural environment, allowed them to choose between various raw materials, production and embellishment techniques in order to achieve the desired result. Differences in the qualities were produced in order to respond to the needs of all social classes.